IMPLEMENTASI SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM PENINGKATAN KINERJA GURU DI SDN 55 MATTIROWALIE KECAMATAN MANIANGPAJO KABUPATEN WAJO - Nisba Pawe; Darmawan; Burhanuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of academic supervision by the school principal in improving teacher performance at SDN 55 Mattirowalie, Maniangpajo Subdistrict, Wajo Regency. This study employs a qualitative approach using a case study design to gain an in-depth understanding of the academic supervision process carried out at the school. Data collection was conducted through in-depth interviews, participatory observation, and document analysis. Data validity was ensured through triangulation of sources and techniques, while data analysis utilized the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that academic supervision is carried out systematically, based on needs, and employs a humanistic, dialogic, and collaborative approach. Supervision serves not only as oversight but as a continuous professional development process. The feedback provided is constructive and followed up with support and training. Academic supervision has been shown to have a positive impact on improving teachers’ performance in planning, implementing, and evaluating learning, and contributes to building a collaborative professional work culture focused on improving the quality of education.